Contribution of HCAHPS Specific Care Experiences to Global Ratings Varies Across 7 Countries: What Can be Learned for Reporting These Global Ratings?. Issue 11 (November 2019) - Orindi, Benedict O.; Lesaffre, Emmanuel; Quintero, Adrian; Sermeus, Walter; Bruyneel, Luk
Abstract : Background: Given the increased international interest in improvement strategies for patient experiences with care, it is important to understand whether the same specific care experiences affect global ratings across countries. Moreover, reporting of these global ratings currently substantially varies in both research and public reporting. Objectives: The objectives of this study were to examine the differential magnitude of associations between Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) specific care experiences and global ratings, and to explore implications for reporting these global ratings. Methods: HCAHPS data were collected from 11, 289 patients across 7 European countries. We studied the association between 11 experience items and 2 global ratings (0–10 hospital rating, hospital recommendation) using multilevel ordered logistic regression analysis. Using interaction terms, we examined consistency of these associations across countries. Assuming homogeneous use and interpretations of response categories of these specific experiences across patients within and between countries, we investigated what the associations between specific experiences and global ratings imply for reporting global ratings across countries. Results: All specific experiences were associated with both global ratings. "Being talked to about care after leaving the hospital" showed the strongest association. There were relatively little differential effects across countries. A reporting strategy with different cutpoints across countries might provide a more equitable comparison of global ratings. Conclusions: Our findings highlight a differential contribution of HCAHPS specific experiences to overall ratings across countries. Research and public reporting may consider examining in more detail within and across populations global rating cutpoints that represent the same true level of positive patient experiences. Abstract : Supplemental Digital Content is available in the text.